ANALISIS SIRKULASI UDARA PADA TANAMAN KOPI BERDASARKAN TINGKAT KEKASARAN TUMBUHAN DAN POLA TANAM GRAF TANGGA PERMATA MENGGUNAKAN METODE VOLUME HINGGA - Riastutik, Ervin Eka; Dafik, D; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2015)
Abstract. Coffee beans are one of Indonesian main export commodities. It can be seen from the amount of coffee exported to other countries, especially Europe. However, the vast area of coffee plantation does not make the productivity of the coffee beans become maximum. There are several factors which influence this condition. One of them is the cropping pattern of coffee plant and the air circulation that affect the pollination process of coffee flower. In this research, an air condition models was designed to solve the problem by employing Volume Hingga method. The models were designed based on the level of plant roughness, distance between coffee plants, and the cropping pattern of coffee (Diamond Ladder Graph). The results of the research is the mathematical models that influenced the level of plant roughness and the cropping pattern of coffee with angle. The symbol of plant roughness in this model is . Coefficient is limited at 0 until 1 (0< <1). The high value of plant roughness coefficient shows the high level of plant roughness. Key Words: coffee plant, air circulation, level of plant roughness, Volume Hingga Method, Diamond Ladder Graph.